Periodic orbits of single neuron models with internal decay rate 0 < β ≤ 1 - Anisimova, Aija; Avotina, Maruta; Bula, Inese (Mathematical Modelling and Analysis, 2013)
In this paper we consider a discrete dynamical systemx n+1=βx n – g(x n ), n=0,1,...,arising as a discrete-time network of a single neuron, where 0